Las herramientas informáticas y la inclusión de los artesanos calificados del cantón Bolívar en la contratación pública en el Ecuador período 2023 - Vivanco Ortega, Germania Beatriz (2025)
The research titled "Information Tools and the Inclusion of Qualified Artisans of Bolívar Canton in Public Procurement in Ecuador, 2023" aims to analyze the impact of technological tools on the active participation of artisans in public procurement processes during the year 2023. The current situation of artisans in the Single Supplier Registry is identified, and the main needs and challenges they face are diagnosed, including limitations in the use of digital tools. The methodology is based on descriptive and bibliographic research, complemented by field research through interviews and surveys conducted with artisans and public entities. In this way, the results indicated the importance of recognizing and strengthening the use of information tools, as these represent one of the main obstacles faced by artisans. Based on these findings, an improvement plan was developed, which includes training strategies, awareness-raising among authorities, and the creation of digital platforms to promote the inclusion and recognition of artisans. This plan seeks to guarantee equal opportunities and increase the participation of qualified artisans in public procurement, contributing to local economic development and the preservation of the artisanal tradition in Bolívar canton. In conclusion, the research highlights the need for public policies that promote transparency and equity in public procurement processes, as well as the use of information tools to facilitate the inclusion of this vulnerable sector.